Effects of Weight Training on Football Skills and Agility of Players - Sevlabhai G. Rathwa; Dr. Gandabhai Amthabhai Desai (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
The purpose of this research study was to study the Effects of Weight Training on Football Skills and Agility of Players. For this research study, only the players who represented the Hemchandracharya North Gujarat University in the inter-college football competition were selected. For this research study, only the players from Sabarkantha district were selected as subjects. In this research study, players of the age group of 17 to 25 years were selected. Only brothers were selected as subjects in this research study. A total of 40 subjects were selected in this research study. Out of which 20 players were divided into the weight training group and 20 players into the control group. The training group was given a total of 12 weeks of training. In which, weight training was given for one hour 3 days a week. In the measurement standard, agility was measured by shuttle run. Analysis of variance, covariance (ANCOVA) was applied to the data obtained from the experimental group and the control group and the significance was tested at the 0.05 level. The conclusion was as follows. A significant improvement was observed in the agility test performance of the subjects selected from the twelve (12) week weight training program of the method.